El abad don Juan, señor de Montemayor : la "historia" de un "cantar" - Martínez Pereira, Ana; Infantes, Víctor (Medievalia Hispanica, 2012)
This edition of the History of Abbot Don Juan de Montemayor rescues one of the most famous medieval legends and disseminating literary relations between Spain and Portugal, formulated in an uncertain date between the twelfth and thirteenth centuries. His argument, with a mixture of relatively historic events and fabulous, could be grounds for an epic poem now lost, by the end of the fifteenth century, through some prosification and a summary. In Summary record of the chronicler Diego Rodriguez de Almela, gave rise to a narrative in the mainstream publishing of romances, that printing spread to readers fans of this genre. He published numerous times throughout the sixteenth and seventeenth centuries, along with other texts with similar characteristics of: Fernan Gonzalez Cid, Queen Sevilla, Charlemagne, etc., Constituting a repertoire novelistic tradition publishing and reading. The lack of affordable modern edition of the work, after which prepared Ramón Menéndez Pidal in the early twentieth century, again advised to prepare the text for modern readers, with the collation of all known witnesses, noting the linguistic and cultural a medieval writing and offering an introduction to the historical and literary details of the gestation of the Man and His most important literary events.